Low molecular weight chitosan conjugated with folate for siRNA delivery in vitro: optimization studies - Shi Q (Dove Medical Press, 2012)
Julio C Fernandes,1 Xingping Qiu,2 Francoise M Winnik,2 Mohamed Benderdour,1 Xiaoling Zhang,3 Kerong Dai,3 Qin Shi11Orthopaedics Research Laboratory, Research Centre, Sacré-Coeur Hospital, 2Department of Physical Chemistry and Polymer Science, Faculty of Pharmacy, University of Montreal, Montreal, Quebec, Canada; 3Orthopaedic Cellular and Molecular Biology Laboratories, Institute of Health Sciences, Chinese Academy of Sciences, Shanghai Jiao Tong University School of Medicine, Shanghai, ChinaAbstract: The low transfection efficiency of chitosan is one of its drawbacks as a gene delivery carrier. Low molecular weight chitosan may help to form small-sized polymer-DNA or small interfering RNA (siRNA) complexes. Folate conjugation may improve gene transfection efficiency because of the promoted uptake of folate receptor-bearing cells. In the present study, chitosan was conjugated with folate and investigated for its efficacy as a delivery vector for siRNA in vitro. We demonstrate that the molecular weight of chitosan has a major influence on its biological and physicochemical properties, and very low molecular weight chitosan (below 10 kDa) has difficulty in forming stable complexes with siRNA. In this study, chitosan 25 kDa and 50 kDa completely absorbed siRNA and formed nanoparticles (≤220 nm) at a chitosan to siRNA weight ratio of 50:1. The introduction of a folate ligand onto chitosan decreased nanoparticle toxicity. Compared with chitosan-siRNA, folate-chitosan-siRNA nanoparticles improved gene silencing transfection efficiency. Therefore, folate-chitosan shows potential as a viable candidate vector for safe and efficient siRNA delivery.Keywords: nonviral vector, chitosan, gene delivery, folate-targeted, siRNA